Electrochemical Immunosensor Using COOH-Functionalized 3D Graphene Electrodes for Sensitive Detection of Tau-441 Protein - Sophia Nazir; Muhsin Dogan; Yinghui Wei; Genhua Pan (Biosensors, 2025)
Early diagnosis of Alzheimer’s disease (AD) is essential for effective treatment; however current diagnostic methods are often complex, costly, and unsuitable for point-of-care testing. Graphene-based biosensors offer an alternative due to their affordability, versatility, and high conductivity. However, graphene’s conductivity can be compromised when its carbon lattice is oxidized to introduce functional groups for biomolecule immobilization. This study addresses this challenge by developing an electrochemical immunosensor using carboxyl-modified commercial graphene foam (COOH-GF) electrodes. The conductivity of graphene is preserved by enabling efficient COOH modification through π–π non-covalent interactions, while antibody immobilization is optimized via EDC-NHS carbodiimide chemistry. The immunosensor detects tau-441, an AD biomarker, using differential pulse voltammetry (DPV), achieving a detection range of 1 fM–1 nM, with a limit of detection (LOD) of 0.14 fM both in PBS and human serum. It demonstrates high selectivity against other AD-related proteins, including tau-217, tau-181, amyloid beta (Aβ1-40 and Aβ1-42), and 1% BSA. These findings underscore its potential as a highly sensitive, cost-effective tool for early AD diagnosis.